2020
DOI: 10.1002/phar.2442
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Kinetic Glomerular Filtration Rate in Adults with Stable and Unstable Kidney Function: Vancomycin as the Motivating Example

Abstract: Background Equations used to estimate kidney function for drug dosing rely on the assumption of homeostasis to translate a single‐point measurement of serum creatinine into clearance (CL). Our objective was to rank order the performance of alternate kidney function equations as predictors of drug CL in stable and unstable patients. Methods Data were extracted from medical records at a single center for all adult patients treated with vancomycin over a 5‐year period for population pharmacokinetic analysis. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Central to this limitation is the recognition that eGFR and eCrCL equations are based on the assumption of homeostasis in creatinine production and elimination that allows for translation of a single steady‐state measurement of SCr to CL. This assumption may be false in many patients with acute infections 15 . Studies have shown that alternate kinetic functions of eGFR such as the Chen model and Chiou model are better than time‐invariant models of vancomycin CL 15,28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Central to this limitation is the recognition that eGFR and eCrCL equations are based on the assumption of homeostasis in creatinine production and elimination that allows for translation of a single steady‐state measurement of SCr to CL. This assumption may be false in many patients with acute infections 15 . Studies have shown that alternate kinetic functions of eGFR such as the Chen model and Chiou model are better than time‐invariant models of vancomycin CL 15,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…This assumption may be false in many patients with acute infections. 15 Studies have shown that alternate kinetic functions of eGFR such as the Chen model and Chiou model are better than timeinvariant models of vancomycin CL. 15,28,29 We did not have the data available to us in this study to explore this major point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 describes the studies evaluating the KeGFR approach in critically ill patients, a population with frequently changing kidney function. 15,21-26 All the studies based the KeGFR calculations on the method of Chen. 10 Based on the results of these investigations, we suggest that standard methods be used when SCr is stable with only minor fluctuation.…”
Section: Studies Evaluating Kinetic Estimates Of Clearancementioning
confidence: 99%